Unlocking the world of intermediate macroeconomics: theory, policy, and economic insights / Dr. Muhammad Hanif Othman - Othman, Muhammad Hanif (Universiti Teknologi MARA, Kedah, 2024)
Intermediate Macroeconomics (ECO557) is a specialized and advanced academic offering tailored for fourth-year students pursuing a degree in economics at UiTM Kedah. The main aim of this course is to provide students with a thorough comprehension of a wide range of macroeconomic ideas. The intermediate macroeconomics course provides an overview of the theoretical modeling of general equilibrium in an economy at a macroeconomic level.